A prática dos professores de música das escolas municipais de São Carlos/SP: uma análise sobre a utilização de uma proposta curricular - Abramovic, Bruno (2024)
This study, based on a qualitative paradigm, is an exploratory investigation that aims to examine how the curricular proposal by Machado et al. (2022) has been utilized by music teachers in the early years of elementary education in the municipal schools of São Carlos/SP. Specifically, the research seeks to analyze the knowledge objects and musical language skills that teachers consider important to develop, as well as those they are able to develop, and to identify the methodological principles of music education that teachers regard as relevant in their pedagogical practice. This research employs semi-structured interviews as the data collection instrument and content analysis as the tool for categorizing and analyzing the data, following the conceptual framework proposed by Gomes (1994) and Sacristán (2013, 2017), with a theoretical reference within the framework of curriculum as a process and praxis, specifically focusing on the points referred to as “curriculum interpreted by teachers and materials” and “Curriculum Modeled by Teachers.” Seven interviews were conducted with seven permanent teachers in the municipal education system of São Carlos/SP. The interviews were transcribed, and sensitive data that could identify the research participants were omitted; each interviewed subject was assigned a female pseudonym, regardless of their gender or gender identity. All participants in this research are part of the group of educators responsible for teaching music in the municipal schools of São Carlos/SP. The research results revealed different attitudes towards the use of Machado et al.'s (2022) curricular proposal, showing varying degrees of depth across different teaching-learning contexts. Among the seven teachers, four use the curricular proposal sporadically, one employs it systematically in their planning, and two do not use it regularly. It was also found that, to some extent, all the teachers, whether consciously or unconsciously, address aspects of the curricular proposal with an emphasis on knowledge objects and skills related to the Elements of Music Language and show varying concentrations in other areas of Machado et al.'s (2022) curricular proposal. Additionally, the teachers’ statements revealed methodological principles of a political nature, viewing music as a tool for occupying various school spaces, and recognizing access to music education as a student right. Furthermore, the research identified a significant degree of curricular modeling in the teachers' practice and a minimal presence of regulatory power exerted by the curriculum.